2014
DOI: 10.1007/s00701-014-2252-0
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the spinal dorsal root entry zone: its clinical significance

Abstract: The detailed anatomy of the variations of the PLS and the average number of rootlets at each spinal level can increase the success of regional surgery. Further, fine measurements on histological sections can give detailed knowledge on the size necessary for lesioning in DREZ operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
(30 reference statements)
0
14
0
1
Order By: Relevance
“…found that the average number of dorsal thoracic rootlets is 6.6 ± 0.8, which is higher than what Sindou found. [1718] They counted 4–5 dorsal thoracic rootlets easily separated and identifiable. The interval between the thoracic nerve rootlets at each level is increased compared to the cervical and lumbosacral levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…found that the average number of dorsal thoracic rootlets is 6.6 ± 0.8, which is higher than what Sindou found. [1718] They counted 4–5 dorsal thoracic rootlets easily separated and identifiable. The interval between the thoracic nerve rootlets at each level is increased compared to the cervical and lumbosacral levels.…”
Section: Resultsmentioning
confidence: 99%
“…found an average of 6.8 T1 segment rootlets in their study which corresponded with the results of three other separate studies. [15181920] In addition, they found that T1 segment contained the largest number of thoracic nerve rootlets, in contrast to the T6, T7, and T10 segments which contained the fewest. [19] Kirazli et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Essa alteração é compatível com aquela provocada pela DREZotomia, com uma extensão máxima de 2,54 mm no corte axial, representando 43,4% da espessura total da medula nessa trajetória. Tal extensão da lesão cirúrgica na DREZ é compatível com aquela relatada por outros autores (2,0 a 3,0mm) [1][2][3]5,8,9,[11][12][13][14][15][17][18][20][21][22][24][25][26][27]29,34,36,37,[41][42][43] . Observa-se, ainda, Não se observam as raízes ou nervos espinhais nos níveis C6 e C7.…”
Section: Discussionunclassified
“…These rotating currents may reflect the summation of synaptic activity and currents from the dorsal column pathway. However, considering the complexity of the entry zone of the spinal nerve root into the spinal cord 4951 , further investigation is needed.…”
Section: Discussionmentioning
confidence: 99%